Perceived Stigmatization Levels of Patients with Tuberculosis Applying to Tuberculosis Dispensaries in Istanbul - (:unkn) unknown (MARMARA UNIV, INST HEALTH SCIENCES, 2019)
Objective: In Turkey, tuberculosis (TB) is considered to be one of the formerly known social diseases. Similar researches exists for AIDS in many countries. There are very few publications about the tuberculosis stigma in our country at international level. This study aimed to assess tuberculosis-related stigma levels and associated factors in patients with tuberculosis applying to tuberculosis dispensaries. Methods: This descriptive study was conducted in two different tuberculosis dispensaries at Istanbul. We used the stigmatization scale for patients with tuberculosis to assess and compare stigma levels of our study population. Nonparametric statistical tests were used for comparison of stigma scores. Results: In our study population, stigmatization because of tuberculosis was found to be related to low income, pulmonary involvement, occupation, and nonexistence of a relative with tuberculosis in the close environment. Conclusion: Combating the causes of stigmatization can assist patients in accessing their healthcare provider. Patients would be more likely to abide by the treatment schedule, thus reducing tuberculosis resistance in the community and decreasing its spread.
Keywords: Dispensary; Istanbul; stigma; tuberculosis; Turkey; TB-RELATED STIGMA; SOCIAL-PSYCHOLOGY